Manifestasi COVID-19 pada Neurologi - Laily Irfana (PROCEEDING UMSURABAYA, 2020)
AbstractSince its appearance at the end of 2019 until now, COVID-19 has spread to all over the worldincluding Indonesia, which is still battling the virus infection with numbers that have notdecreased. In its journey, COVID-19 has manifested itself in various body systems, includingthe nerves. Many case reports and studies mentioned neurological clinical symptoms inCOVID-19 patients, ranging from mild ones such as headaches, anosmia, to severe symptomssuch as stroke, meningitis, to Guillain Barre Syndrome. This article discusses how SARS-CoV-2 can reach the nervous system, and what neurological manifestations can occur, sourced fromvarious retrospective studies, reviews, and case reports.Keywords: COVID-19, nervus system, neurology clinical symptoms